Gabapentin and intraoperative hypotension - J. H. Patrick; J. D. Tobias (Pediatric Anesthesia and Critical Care Journal, 2021)
Gabapentin is commonly used perioperatively as an ad-junct to decrease opioid requirements and hence opioid- related adverse effects. Despite its widespread use, re- cent information has provided concern regarding its ad- verse effect profile. Perioperative gabapentin administration has been associated with greater incidence of dizzi- ness, visual disturbances, and increased risk for postoperative pulmonary complications. We present a 13-year- old female who experienced intraoperative hypotension which was eventually attributed to the preoperative ad- ministration of gabapentin. The perioperative use of gabapentin is discussed, its adverse effect profile reviewed, and its potential role in perioperative blood pressure changes presented.